Compressive Strength of Foamed Concrete with a density of 55kg/m3 based on Sodium Lauryl Sulfate - Carrion Rabanal, Katia Nataly; Carrero Llatas, Mahily Najely; Goicochea Huaman, Héctor Jesús; Quiroz Infante, Fran Yhonny; Gaona Abanto, Erick Andres Emilio (LACCEI, 2024)
The study is based on adding sodium lauryl sulfate to generate a lightweight concrete, the objective was to investigate the effect that the foaming agent generates on the resistance of the concrete. A total of 6 cylindrical concrete specimens were made, 3 with the addition of foam with a density of 55kg/m3 and 3 without the addition of foam. The specimens were removed from the formwork 24 hours after production to be immersed in water for curing for 28 days and then the compression test was carried out and compared between both types of concrete. The results of the concrete with foam addition had a slump of 2.7 inches, its weights were 10.6 kg, 10.7 kg and 10.9 kg and its compressive strength at 28 days was 95.6 kg/cm2, 96.9 kg/cm2, cm2 and 97.5 kg/cm2; The results of concrete without foam addition, slump of 1.2 inches, with weights of 12.1 kg, 12.5 kg and 12.6 kg, the resistance achieved after 28 days was 185.5 kg/cm2, 186.7 kg/cm2 and 192.3 kg/cm2 . It is inferred that the addition of Sodium Lauryl Sulfate has a negative impact on the compressive strength of concrete. These observations highlight the importance of considering the use of admixtures to produce concrete with new specifications.